2011
DOI: 10.1021/ja209276a
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline-Alkaline Earth Fluoride Carbonate Crystals ABCO3F (A = K, Rb, Cs; B = Ca, Sr, Ba) as Nonlinear Optical Materials

Abstract: A new series of alkaline-alkaline earth fluoride carbonates (KSrCO(3)F, RbSrCO(3)F, KCaCO(3)F, RbCaCO(3)F, CsCaCO(3)F, and Cs(3)Ba(4)(CO(3))(3)F(5)) were synthesized by spontaneous crystallization with molten fluxes. Their crystal structures, except for Cs(3)Ba(4)(CO(3))(3)F(5), exhibit the stacking of [AF](∞) (A = K, Rb, Cs) and [B(CO(3))](∞) (B = Ca, Sr) layers, and the coplanar alignment of [CO(3)] triangles. The results from the UV-vis diffuse reflectance spectroscopy study of the powder samples indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
305
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 465 publications
(315 citation statements)
references
References 50 publications
7
305
0
3
Order By: Relevance
“…There is a medium-weak band at 680−775 cm -1 , which corresponds to the bending vibration of δ-(OCO) of (CO 3 ) 2-groups. 27 Figure 2. Coordination environments of Eu (a) and Na (b) atoms.…”
Section: Crystal Structurementioning
confidence: 99%
“…There is a medium-weak band at 680−775 cm -1 , which corresponds to the bending vibration of δ-(OCO) of (CO 3 ) 2-groups. 27 Figure 2. Coordination environments of Eu (a) and Na (b) atoms.…”
Section: Crystal Structurementioning
confidence: 99%
“…Rojas et al [21] reported that calcium borate glasses are useful for application as thermo luminescent dosimeter. Non-linear optical (NLO) properties of the alkaline earth materials were studied by Zou et al [22] and found that these materials are suitable for non linear optical and ultraviolet applications. The above literature survey suggests that the alkaline earth oxy-halide borate glasses are of technological importance.…”
Section: Introductionmentioning
confidence: 99%
“…Ultraviolet (UV) nonlinear optical (NLO) crystals can be considered as a clean energy source for processing of materials, and also play an important role in laser science and technology [3]. Many efforts have been directed towards understanding the relationship between the composition, structure, and NLO properties of crystals, which are critical in the development of new NLO crystals [4].…”
Section: Introductionmentioning
confidence: 99%